2023
DOI: 10.1136/ard-2023-223845
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor agonists as a disease-modifying therapy for knee osteoarthritis mediated by weight loss: findings from the Shanghai Osteoarthritis Cohort

Abstract: ObjectiveObesity is a risk factor for knee osteoarthritis (KOA) development and progression. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are indicated for type 2 diabetes mellitus (T2DM) and obesity. However, whether KOA patients can benefit from GLP-1RA therapies has not been sufficiently investigated, especially in the long term.MethodsThe Shanghai Osteoarthritis Cohort study is a prospective, observational, multicentre study of >40 000 adults with clinically diagnosed osteoarthritis aged >45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Glucagon-like peptide-1 receptor agonists (GLP-1RAs), including semaglutide, liraglutide, and dulaglutide, are a newly emergent class of weight-reducing drugs ( 44 ). A multicenter prospective study revealed that GLP-1RAs acted as disease-modifying drugs for KOA patients mediated by weight loss ( 2 ). Future research may need to pay more attention to this class of game-changing drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucagon-like peptide-1 receptor agonists (GLP-1RAs), including semaglutide, liraglutide, and dulaglutide, are a newly emergent class of weight-reducing drugs ( 44 ). A multicenter prospective study revealed that GLP-1RAs acted as disease-modifying drugs for KOA patients mediated by weight loss ( 2 ). Future research may need to pay more attention to this class of game-changing drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Knee osteoarthritis (KOA) is a prevalent and disabling disease characterized by the structural degradation of cartilage, persistent pain, joint stiffness, and functional limitations, affecting more than 10% of the overall population as estimated (1)(2)(3). According to the Global Burden of Disease Study 2019 (4), because of the increase in the aging population, the disease burden of KOA has been rapidly growing worldwide over the past decades (5).…”
Section: Introductionmentioning
confidence: 99%
“…They compared the level of pain, the velocity of cartilage degradation as measured by MRI and the number of knee surgeries among patients with diabetes with knee OA treated or not with GLP1RAs. They observed a significant association between GLP1RA use and all endpoints 19. Interestingly, because of the other property of these molecules to facilitate weight loss, they looked at this causal role in mediating this association and found that only 31% of this association was mediated by weight loss suggesting an additional direct effect on joints.…”
Section: Treatmentsmentioning
confidence: 99%
“…A new class of medications (GLP-1 antagonists) have emerged with good efficacy and low side effects profile for losing weight, which could be considered. The Shanghai Osteoarthritis Cohort study prospectively followed >40 000 adults above 45 years with clinically diagnosed OA and concluded that GLP-1RA in sufficient treatment duration could be knee OA disease-modifying in patients with diabetes, possibly through weight loss [47]. However, they found a need for more investigations to clarify the effects on joint structure, disease process, and patient-reported outcomes.…”
Section: Medicationsmentioning
confidence: 99%